Delayed Cord Clamping in Preterm Neonates: A Review of Benefits and Risks. Issue 1 (January 2016) - Brocato, Brian; Holliday, Nicolette; Whitehurst, Richard M.; Lewis, David; Varner, Stephen
Abstract : Importance: Delayed clamping of the umbilical cord of premature neonates decreases perinatal morbidity. Allowing time for autotransfusion of placental blood before the umbilical cord is clamped represents a simple practice that may have significant impact. In light of many professional societies recommending delayed cord clamping in premature neonates because of its beneficial effects, the topic still holds many unanswered questions. Objective: The purpose of this article is to review the most recent evidence available regarding delayed cord clamping in premature neonates. Evidence Acquisition: A literature search using PubMed, Cochrane database, and cumulative index of nursing and allied health literature provided the references for this review. Results: Although the evidence comes primarily from small trials, delayed umbilical cord clamping in premature neonates is associated with less need for red blood cell transfusions, increase in hemoglobin and hematocrit levels, and decrease in risk of intraventricular hemorrhage and necrotizing enterocolitis. No maternal or neonatal risks have been demonstrated. Data on long-term outcomes are lacking. Conclusions and Relevance: Delayed cord clamping in premature neonates is a simple procedure that the current evidence supports to improve neonatal morbidity. The impact on long-term outcomes remains limited. The optimal time to delay cord clamping and potential risks are poorly studied. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner will be better able to: review the most current, available evidence of the topic of delayed cord clamping in premature neonates; learn the benefits that have been demonstrated to decrease morbidity of premature neonates exposed to delayed cord clamping; discuss the potential risks of delayed cord clamping and clinical scenarios that may predispose the infant to these risks; and identify what still remains unknown about the risks and benefits of delayed cord clamping in premature neonates.